Foreign aid and sustainable inclusive human development in Africa - Simplice Asongu; Joseph Nnanna (African Governance and Development Institute (AGDI), 2018)
Motivated by evidence that extreme poverty has been decreasing in all regions of the world with the exception of Africa, the study contributes to the literature on reinventing foreign aid by assessing if development assistance can sustain inclusive human development. The empirical evidence is based on 53 African countries with data for the period 2005-2012 and Generalised Method of Moments. The adopted foreign aid variables include: aid for social infrastructure, aid for economic infrastructure, aid to the productive sector, aid to the multi sector, programme assistance, action on debt and humanitarian assistance. The results reveal that whereas foreign aid improves inclusive human development in the short-run, it decreases it in the long term. Policy implications are discussed with particular emphasis on reinventing foreign aid for sustainable development in the post-2015 development agenda.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Sustainable Development; Africa